A Conserved Carbon Starvation Response Underlies Bud Dormancy in Woody and Herbaceous Species - Tarancón, Carlos; González-Grandío, Eduardo; Oliveros, Juan C.; Nicolas, Michael; Cubas, Pilar (Frontiers in Plant Science, 2017)
Plant shoot systems give rise to characteristic above-ground plant architectures. Shoots are formed from axillary meristems and buds, whose growth and development is modulated by systemic and local signals. These cues convey information about nutrient and water availability, light quality, sink/source organ activity and other variables that determine the timeliness and competence to maintain development of new shoots. This information is translated into a local response, in meristems and buds, of growth or quiescence. Although some key genes involved in the onset of bud latency have been identified, the gene regulatory networks (GRNs) controlled by these genes are not well defined. Moreover, it has not been determined whether bud dormancy induced by environmental cues, such as a low red-to-far-red light ratio, shares genetic mechanisms with bud latency induced by other causes, such as apical dominance or a short-day photoperiod. Furthermore, the evolution and conservation of these GRNs throughout angiosperms is not well established. We have reanalyzed public transcriptomic datasets that compare quiescent and active axillary buds of Arabidopsis, with datasets of axillary buds of the woody species Vitis vinifera (grapevine) and apical buds of Populus tremula x Populus alba (poplar) during the bud growth-to-dormancy transition. Our aim was to identify potentially common GRNs induced during the process that leads to bud para-, eco- and endodormancy. In Arabidopsis buds that are entering eco- or paradormancy, we have identified four induced interrelated GRNs that correspond to a carbon (C) starvation syndrome, typical of tissues undergoing C depletion. This response is also detectable in poplar and grapevine buds before and during the transition to dormancy. In all eukaryotes, C limiting conditions are coupled to growth arrest and latency like that observed in dormant axillary buds. Bud dormancy might thus be partly a consequence of the underlying C starvation syndrome triggered by environmental and endogenous cues that anticipate or signal conditions unfavorable for sustained shoot growth.